10-Molybdo-2-vanadophosphoric acid derived (V) MoS2 microflowers @ V2CTx MXene designed 3D@2D nanoarchitecture for high-performance aqueous supercapacitors. (March 2023) - Kumar, Deepak; Joshi, Akanksha; Marichi, Ram Bhagat; Singh, Gurmeet; Sharma, Raj Kishore
Abstract: Polyoxometalates (POMs) are emerging redox active materials having great potential for energy storage. Normally, POMs are directly anchored to substrates, however we looked into a novel feature of POM chemistry by employing them as precursor for metal sulphide 3D microflower arrangements without the use of a template. High surface area, outstanding electrical conductivity, and exceptional structural stability are all characteristics of 2D materials like MXenes; nevertheless, their direct use is constrained by poor specific capacitance as a result of layer restacking. Transition Metal sulphides (TMDs), on the other hand, have a high surface area but a poor conductivity. Layer restacking will be prevented by an MXene-TMDs nanocomposite, which will also increase TMDs' conductivity. Here, we report MXene-TMDs nanocomposite (MV) with MXene intercalated vanadium molybdenum sulphide (VMD) microflowers using 10-molybdo-2-vanadophosphoric acid. Due to faster ionic diffusion, higher electrochemically active surface area, and more active sites, MV exhibits good electrochemical performance. Additionally, the MV||MV cell offers outstanding cycling stability (96 % capacitance retention after 8000 cycles @ 2 A g −1 ) and performs well up to 0.9 V, delivering a maximum energy density of 28.96 Wh kg −1 @ 232.35 W kg −1 . This research investigates how POMs affect the atomic ratio and morphology of final product. Graphical abstract: Unlabelled Image Highlights: Bimetallic sulphide microflowers derived from 10-molybdo-2-vanadophosphoric acid. 3D@2D interfacial heterostructured TMD@MXene nanocomposite (MV) was synthesized. MV offers faster ionic diffusion, enhanced ECSA and greater number of active sites. Symmetric cell delivers energy density of 28.96 Wh kg −1 @ 232.35 W kg −1 .